The impact of social support on job-related behaviors through the mediating role of job stress and the moderating role of locus of control: Empirical evidence from the Vietnamese banking industry - Ha Nam Khanh Giao; Bui Nhat Vuong; Hasanuzzaman Tushar (Cogent Business & Management, 2020)
The aim of this research is to investigate the effect of social support on job-related behaviors, noting the mediating roles of job stress. Specifically, the study tests the prediction regarding the extent to which these different types of locus of control moderate the relationship between social support and job stress as well. The current study used self-report questionnaires from a sample of employees in the Vietnamese banking industry to test the hypothesis. Results from the partial least squares structural equation modeling (PLS-SEM) using the SmartPLS 3.0 program showed that social support positively impacted job-related behaviors (e.g., job satisfaction, job performance); these relationships were mediated partially through job stress. Besides, this research revealed that individuals with a higher internal locus of control were more likely to have lower levels of job stress and it also moderated the relationship between social support and job stress. This negative association was weaker for bankers who have a higher external locus of control. The main findings of this research demonstrated that social support and locus of control play an important role in the overall effectiveness of employees. It implied that it is crucial for organizations to set up a good work atmosphere that supports psychological well-being and have suitable policies to strengthen social support among supervisors and employees in an organization to reduce job stress and improve job-related behaviors.
Keywords: 650; social support; job stress; job satisfaction; job performance; locus of control